Self-identification of the lyrical subject in Russian poetry (a draft typology) - Andrey Anatolievich Faustov (Enthymema, 2014)
The end goal of this paper is to shed light on the changes in the lyrical subject self-identification logics that were characteristic of Russian poetry of the ‘modernist’ era. We are going to focus our attention exclusively on the poems with a lexically expressed I, which build the nucleus of the poetic fraction of literary texts and allow to get a clear idea about the mechanism of self-naming that we regard as fundamental for self-identification of the lyrical I.